An Analysis of English for Specific Purposes Textbook Entitled Intelligent Bussines Based on Cunningsworth's Theory - Abdul Syahid; Yeni Suryani; Lafifah Suliyya; Fatma; Winna (UNIB Press, 2024)
The development of English language proficiency for specific purposes (ESP) plays an important role in preparing learners for success in an increasingly globalized work environment, particularly in the field of business. In this context, the evaluation of ESP textbooks, such as